The dynamics of violence and revenge in the Hebrew book of Esther - Ruiz-Ortiz, Francisco-Javier, 1976- (Vetus Testamentum, Supplements, 2017)
This volume offers a thematic study of an integral part of the Hebrew text of Esther, namely, violence. In The Dynamics of Violence and Revenge in the Hebrew Book of Esther , Francisco-Javier Ruiz-Ortiz makes the first ever monographic research on the topics of hostility and the mechanisms of revenge as expressed by the author of the Hebrew book of Esther. The present book is divided into two parts consisting of three chapters each. After an introductory chapter reviewing previous studies on the book of Esther, the author analyses the main vocabulary of violence and revenge in this biblical text before studying the narrative of Esther from the point of view of violence. The results of these two avenues of research are then applied on three pericopes which are representative of the dynamics of violence. Each of the chosen texts illustrates how violence and revenge are used by the author to express the message of survival and the importance of the Jewish people.